2020
DOI: 10.1103/physrevd.102.074507
|View full text |Cite
|
Sign up to set email alerts
|

Lattice study of thermodynamic properties of dense QC2D

Abstract: In this paper we study thermodynamic properties of dense cold SUð2Þ QCD within lattice simulation with dynamical rooted staggered quarks which in the continuum limit correspond to N f ¼ 2 quark flavours. We calculate baryon density, renormalized chiral and diquark condensates for various baryon chemical potentials in the region μ ∈ ð0; 2000Þ MeV. It is found that in the region μ ∈ ð0; 540Þ MeV the system is well described by the ChPT predictions. In the region μ > 540 MeV the system becomes sufficiently dense … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…Studies of two-color matter have been performed by several groups [34,[56][57][58][59][60][61][62][63][64]. teal In cold matter, these studies have confirmed that baryonic matter forms at an onset µ o = m π /2, whereupon diquarks start populating the vacuum.…”
Section: Baryon Densitymentioning
confidence: 94%
See 1 more Smart Citation
“…Studies of two-color matter have been performed by several groups [34,[56][57][58][59][60][61][62][63][64]. teal In cold matter, these studies have confirmed that baryonic matter forms at an onset µ o = m π /2, whereupon diquarks start populating the vacuum.…”
Section: Baryon Densitymentioning
confidence: 94%
“…In Ref. [33] as well as in lattice studies [34][35][36][37][38][39][40], the authors consider an idealization with µ I = 0, µ B = 0. Such a system is unstable under weak interactions which do not conserve isospin.…”
Section: Symmetries Of Qcd and Topologymentioning
confidence: 99%
“…Another hint may be obtained from studies in two-color QCD; for this system, lattice MonteCarlo simulations are doable [88][89][90]. There have been seminal works on the phase diagram, EoS, and order parameters.…”
Section: For 5n 0 N B 40nmentioning
confidence: 99%
“…The actual results are displayed in Figure for the ratio of shear viscosity to entropy density η / s as a function of the scaled temperature T / T c for μ B = 0 in comparison to those from lattice QCD (Astrakhantsev et al ). The solid green line ( η Kubo / s ) shows the result from the original DQPM in the Kubo formalism, while the dashed green line η2γnormalRTA/s shows the same result in the RTA (Equation (8)) by replacing Γ i by 2 γ i .…”
Section: Transport Properties Of the Partonic Systemmentioning
confidence: 99%
“…The solid red line ηΓonnormalRTA/s results from Equation (8) using the interaction rate Γ on calculated by the microscopic differential cross sections in the on‐shell limit. The dashed gray line demonstrates the Kovtun–Son–Starinets bound (Kovtun et al ) ( η / s ) KSS = 1/(4 π ), and the symbols show lQCD data for pure SU(3) gauge theory taken from Astrakhantsev et al () (pentagons)…”
Section: Transport Properties Of the Partonic Systemmentioning
confidence: 99%